Pengaruh Transaksi Mobile Banking, Internet Banking, dan ATM terhadap Kinerja Keuangan Perbankan - Tangiduk, Rastieci; Kantohe, Meidy S. S.; Marunduh, Andrew P. (Journal of Culture Accounting and Auditing, 2024)
Banking financial performance experienced increases and decreases in achieving profits, but in this situation, several banks closed branch offices, because the use of digital banking continued to increase. This research aims to determined the effect of mobile banking, internet banking and ATM transactions on banking financial performance. This type of research was descriptive research using secondary data, with a quantitative approach. This research used a purposive sampling method to determined the research sample, so that eight conventional banks were obtained and there were forty samples for research. The data obtained were analyzed using the multiple regression analysis method with a random effect model. The results of this research show that partially mobile banking transactions have a positive effect on ROA. Meanwhile, internet banking transactions have a negative effect on ROA and ATM transactions have a negative effect on ROA. The research results also show that simultaneously, mobile banking transactions, internet banking transactions and ATM transactions have a positive effect on ROA. Keywords: Financial Performance; Mobile banking transactions; Internet banking; ATM